Environmental biodegradability of [14C] single‐walled carbon nanotubes by Trametes versicolor and natural microbial cultures found in new bedford harbor sediment and aerated wastewater treatment plant sludge. (February 2015) - Parks, Ashley N.; Chandler, G. Thomas; Ho, Kay T.; Burgess, Robert M.; Ferguson, P. Lee
Abstract Little is known about environmental biodegradability or biotransformations of single‐walled carbon nanotubes (SWNT). Because of their strong association with aquatic organic matter, detailed knowledge of the ultimate fate and persistence of SWNT requires investigation of possible biotransformations (i.e., biodegradation) in environmental media. In the present study, [14C]SWNT were utilized to track biodegradation over 6 mo by pure liquid culture of the fungus Trametes versicolor and mixed bacterial isolates from field‐collected sediment or aerated wastewater treatment plant sludge. The mixed cultures were chosen as more environmentally relevant media where SWNT will likely be deposited under both aerobic and anaerobic conditions. Activity of [14C] was assessed in solid, aqueous, and 14CO2 gaseous phases to determine amounts of intact SWNT, partially soluble SWNT degradation products, and mineralized SWNT, respectively, during the 6 mo of the experiment. Mass balances based on radiocarbon activity were approximately 100% over 6 mo, and no significant degradation of SWNT was observed. Approximately 99% of the [14C] activity remained in the solid phase, 0.8% in the aqueous phase, and less than 0.1% was mineralized to 14CO2, regardless of culture type. These results suggest that SWNT are not readily biodegraded by pure fungal cultures or environmental microbial communities, and are likely persistent in environmental media. Environ Toxicol Chem 2014;9999:1–5. © 2014 SETAC